2015
DOI: 10.1681/asn.2014070697
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in IgA Nephropathy

Abstract: Current guidelines suggest treatment with corticosteroids (CS) in IgA nephropathy (IgAN) when proteinuria is persistently $1 g/d despite 3-6 months of supportive care and when eGFR is .50 ml/min per 1.73 m 2 . Whether the benefits of this treatment extend to patients with an eGFR#50 ml/min per 1.73 m 2 , other levels of proteinuria, or different renal pathologic lesions remains unknown. We retrospectively studied 1147 patients with IgAN from the European Validation Study of the Oxford Classification of IgAN (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
165
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(187 citation statements)
references
References 33 publications
11
165
2
9
Order By: Relevance
“…It does not recommend use of steroids in subset of patients with eGFR <50 mL/min/1.73 m 2 (3). The use of steroids in patients with eGFR <50 mL/ min/1.73 m 2 has been addressed in the VALIGA study which examined the benefit of steroids in this subset of patients in addition to renin angiotensin system blockers (RASBs) compared with RASBs alone, (particularly in patients with proteinuria >1 g/d), suggesting a value in patients with eGFR <50 mL/min/1.73 m2 as well (11). In our study, group 1 did not benefit in terms of progression of CKD compared to group 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not recommend use of steroids in subset of patients with eGFR <50 mL/min/1.73 m 2 (3). The use of steroids in patients with eGFR <50 mL/ min/1.73 m 2 has been addressed in the VALIGA study which examined the benefit of steroids in this subset of patients in addition to renin angiotensin system blockers (RASBs) compared with RASBs alone, (particularly in patients with proteinuria >1 g/d), suggesting a value in patients with eGFR <50 mL/min/1.73 m2 as well (11). In our study, group 1 did not benefit in terms of progression of CKD compared to group 2.…”
Section: Discussionmentioning
confidence: 99%
“…The KDIGO guidelines make no recommendations for use of corticosteroids (CS) in individuals with an initial eGFR ≤50 mL/min/1.73 m 2 , who are under-represented in majority of the trials (3)(4)(5)(6)(7)(8)(9)(10). The recent analysis from VALIGA study showed that steroids may be of benefit even in this group (11).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis from the VALIGA study showed that 7/184 (3.8%) patients who had received any form of immunosuppression developed ESRD compared to 20/184 (10.8%) of propensity matched patients receiving RAAS blockade alone after mean follow up of 4.7 years [20]. Acknowledging the limitations of a small sample size, observed rates of development of ESRD (5%) in our study could suggest that MMF provides some long-term renal protection.…”
Section: Discussionmentioning
confidence: 56%
“…A large retrospective review of 1147 patients who were part of the European Validation Study of the Oxford Classification of IgAN (VALIGA) cohort identified 184 subjects with greater risk of progression, and propensity matched them to 184 subjects who received RAAS blockade alone. They found that immunosuppression (corticosteroids) in this targeted cohort of patients reduced proteinuria and the rate of renal function decline, and increased renal survival [20]. This suggests that for certain patients at greater risk of progression, immunosuppressive therapy may in fact be indicated.…”
Section: Discussionmentioning
confidence: 72%
“…The current management of patients with acute crescentic rapidly progressive IgA nephropathy includes steroids [29][30][31] and cytotoxic drugs [32,33], though overall renal survival in crescentic IgA nephropathy is significantly inferior to that in other forms of crescentic glomerulonephritis, including systemic vasculitis and Good pasture's disease [7,34]. The use of high dose of intravenous methylprednisolone followed by oral prednisolone and mycophenolate mofetil, in this reported case, was very effective in ameliorating the renal function deterioration and in inducing rapid recovery without dialysis support despite the presence of crescentic glomeruli together with interstitial inflammation and tubular atrophy.…”
Section: Discussionmentioning
confidence: 99%